Diagnosis and treatment of intra-abdominal sepsis: a study of 240 patients at the Hospital Universitario del Valle, Cali (Colombia Medica, 1987)
From patients admitted during the last semester of 1984 to the Hospital Universitario del Valle, Cali, Colombia, with a diagnosis of intraabdominal sepsis, 240 clinical charts were assessed. The age group 15-44 y.o. had the highest number of cases, 48.3%; leucocytosis was common, 66.7%, while jaundice was mentioned in 7.5% of the charts. Chest and abdominal X-rays were carried out in less than 20% of persons; although ultrasound scanning was performed only in 8% of cases, it was helpful for diagnosing intrabdominal abscesses. CAT studies were not done.Intraabdominal abscesses had in Cali the following main causes: 1) perforated acute appendicitis, 2) hollow viscus perforation, #) abdominal trauma, 4) biliary tract diseases, and 5) gyneco-obstetric entities.Surgical treatment was given to each patient; furthermore, 51% of them received a combination of gentamycin and chloramphenicol. Different combinations of antibiotics against aerobic and anaerobic bacteria were prescribed to the rest of the patients. The most common isolated bacterium was Echirichis coli. Overall, all mortality was 10.8%, and the average hospital stay was 13.3 days.